The role of school libraries in the educational process and its impact on school students - Al-Braihi, Samer Nseeb Hamad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to demonstrate the importance and impact of school libraries in developing the educational process, and refining the students’ personality, through the various services that libraries provide from providing an appropriate academic atmosphere to providing various information and various sciences, which in their entirety positively affect the entire educational and educational process.The researcher used the analytical method, as he reviewed many references, research and previous studies, and analyzed the information and concepts they contain related to the subject of the study in order to reach an answer to the study’s questions and problems and to come up with results and recommendations that serve the study, and the study reached the following results: The educational process and school students’ results are closely related It is closely related to the school library as it supports the educational process, as well as the school curriculum and its activities integrate horizontally with the library activities and enhance them.
Keywords: school library; educational process; schools; students